Peran Ayah dalam Pengasuhan dan Kecerdasan Matematis Siswa di SD Negeri Padang Bujur Sipirok - Yulia Anita Siregar; Winmery Lasma Habeahan; Muhammad Huda Firdaus (Departement of Mathematics Education, 2023)
The research was conducted at SD N Padang Bujur in Sipirok District. The study used Spearman's rank correlation research. The aims of the study were to: Know the relationship between the father's role in parenting and Mathematical Intelligence in Students of SD N Padang Bujur Sipirok. This study resulted in an average father's role in parenting of 99.28 while the average mathematical intelligence was 97.28. From the results of the analysis calculations in answering the research hypothesis, it is obtained ρ count = 0.995 with a very strong category and ρ table = 0.339. So it can be concluded that there is a significant relationship between the father's role in parenting and Mathematical Intelligence in SD N Padangbujur Sipirok students with a contribution of 99%. This means that the role of fathers in parenting is needed in shaping students' mathematical intelligence.